Effects of intermittent fasting combined with exercise on serum leptin and adiponectin in adults with or without obesity: a systematic review and meta-analysis of randomized clinical trials - Kazeminasab, Fatemeh; Behzadnejad, Nasim; Cerqueira, Henrique S.; Santos, Heitor O.; Rosenkranz, Sara K. (Frontiers in Nutrition, 2024)
Context Intermittent fasting (IF) and exercise training (Exe) have been evaluated in several studies for improving cardiometabolic biomarkers related to weight loss. However, further investigation is required to understand the potential effects on leptin and adiponectin concentrations. IF protocols have been shown to be efficient in improving adipokines, but further research is required to determine whether or not IF regimens combined with Exe are superior to Exe alone. Objective The aim of this study was to determine whether or not interventions combining IF plus Exe are more effective than Exe only for improving serum leptin and adiponectin in adults with and without obesity. Data Extraction A systematic review and meta-analysis was performed by searching PubMed, Scopus, and Web of Science databases up to August 2023 for randomized clinical trials that determined the effects of IF plus Exe vs. Exe alone (control) on body weight, serum leptin, and serum adiponectin. Analyses were conducted for IF plus Exe vs Exe alone to calculate weighted mean differences (WMD) and standardized mean differences (SMD). Analysis The current meta-analysis included 6 studies with a total sample of 153 participants, with intervention durations ranging from three days to 52 weeks. IF plus Exe elicited significantly larger decreases in leptin levels [SMD=-0.47, p=0.03], which were accompanied by weight loss [WMD=-1.25 kg, p=0.05], as compared with exercise-only interventions, but adiponectin did not differ between the two [SMD=0.02, p=0.9]. Conclusion IF combined with Exe reduced leptin significantly, but did not change adiponectin levels, when compared to exercise only. Perhaps these reductions in leptin levels may have been associated with weight loss; however, due to the small number of included studies and the high heterogeneity in the weight loss outcomes, this result is uncertain.